2019
DOI: 10.25165/j.ijabe.20191205.5206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regulated deficit irrigation on the growth and berry composition of Cabernet Sauvignon in Ningxia

Abstract: The adoption of water-saving irrigation strategies is required particularly for wine grape variety, which has been widely cultivated in arid and semiarid areas. To assess vine response to regulated deficit irrigation (RDI), the grape growth and berry composition under five treatments that irrigated at a certain percentage of the crop evapotranspiration (ET c) were evaluated over a 3-year period in a vineyard with the grape variety of Cabernet Sauvignon. The results indicated that RDI had a significant effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Studies on the physiology of drought stress in grapevine revealed that a water de cit would increase the accumulation of phenolic contents in grapes, which is detrimental to yield production (Egea et al, 2010, Santesteban et al, 2011, García et al, 2012, Wang et al, 2019. Drought stress could lead to stomatal closure, which negatively affects the gas exchange in plants and the metabolism of plants (Jones et al, 1991, Chen et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the physiology of drought stress in grapevine revealed that a water de cit would increase the accumulation of phenolic contents in grapes, which is detrimental to yield production (Egea et al, 2010, Santesteban et al, 2011, García et al, 2012, Wang et al, 2019. Drought stress could lead to stomatal closure, which negatively affects the gas exchange in plants and the metabolism of plants (Jones et al, 1991, Chen et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Over 1000 VOCs have been discovered, with several of them proving to have a substantial impact on wine fragrance [1] . The composition of VOCs is relevant to grape variety, climate, soil, and, most importantly, the brewing techniques (fermentation and aging) [2,3] .…”
Section: Introduction mentioning
confidence: 99%